New records of exotic spiders and insects to the Azores, and new data on recently introduced species - Borges, Paulo A. V. (2013)
The introduction of exotic species in islands is recognized as a major threat to native biota and ecosystems. In this contribution we list thirteen widespread exotic invertebrate species (two Araneae, one Orthoptera, four Hemiptera, four Coleoptera and two Diptera) that were recorded from the Azorean Islands in the last few years for the first time. In addition, we list another ten invertebrate species (two Araneae, one Orthoptera, two Phasmatodea, one Hemiptera, three Coleoptera and one Diptera) that expanded their known range in the archipelago. The pathways of entrance for species in the Azores, their impact on the local economy and biodiversity, as well as strategies to halt the introduction of alien species are discussed.